Aspects of climatic factors and the need of irrigation: Case study; Brăila County - Elisabeta Roşu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Climate describes the temperature, precipitation and other weather condition. Climate modification by the progressive warming of the atmosphere resulting from the concerted action of several factors, both natural and anthropic favours the diminution of precipitations at soil level, corroborated with the increase of temperatures. The climate became a constraining factor in the growth and development of crops, its influence being pregnant both in the allocation and use of water resources in agriculture. The phenomena of dryness and drought represent a natural aspect of the continental climate that manifest in the South-East part of Romania. The present study refers to the influence of weather factors and the need of irrigation in the county Bræaila.
Keywords: 330; climatic factors; soil; water resources; irrigations